Cancellations, observations, inspirations: 125 years of the Swiss National Library: An anniversary in the time of Corona. Issue 2 (August 2020) - Mangold, Hannes
Two days after the Swiss National Library's anniversary exhibition opened, it was forced to close down again because of the coronavirus. Thereafter, the focus switched to communicating content prepared for the exhibition via the National Library's own website and other external websites. Meanwhile, the book 125 Years of the Swiss National Library proved ideally suited to continuing the anniversary celebrations despite the omnipresent virus.